In memoriam da liberdade: história comum de jovens negros em cumprimento de medidas socioeducativas - Andrade, Alice Bispo Fernandes de (Universidade Federal de São Carlos, 2021)
In this study, racism is considered an important element of discrimination and racialization of young male bodies, pointing their life experience to marginalization and the criminal stigma. Based on the socio-educative measures formulation and the racial studies, this research aimed to comprehend and analyze how race and masculinity impact young-black-boys under socio-educative measures. For that, the research methodology was Oral History. Four young-black-boys participated in the investigation and co-production of the data. The boys are self-declared black or brown (mixed race) and male gender, and one being under socio-educative measures without freedom restraint and three egresses. Four interviews were conducted, one with each young person, intermediated by a script, with triggering questions that helped to capture the young person’s story. The interviews were transcribed and turned into narratives, which were analyzed using the content analysis technique. After deepening the interviews, three categories were chosen, described and analyzed in this study: I. Take the vision that minor will speak: what is it like to be a black young?; II. All positivity rowing against the tide: Socio-educative Measures Program (PMSE) without freedom restraint and family as support; III. Always with their feet on the floor, progress will come: young’s dreams and self-places. According to the results, it is possible to comprehend race and black masculinity as markers in the world experience of young people as well as in the judgment of socio-educative measures. Despite many violations, PMSE and family emerge as support and space to increase social participation. In addition, the research pointed out the importance of facilitating spaces and mechanisms for young people to tell their own history. It is considered that this research contributes to academic studies about black-young-males who have been in conflict with the law at any point in their lives, based on the critical perspective that touches ethinic racial and masculinity issues from the point of view of young young boys.
In memoriam of freedom: histories of black young males under socio-educative measures
Keywords: Juventude; Medidas socioeducativas; Negro; Masculinidade; Youth; Socio-educative measures; Black man; Masculinity; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA